Application of Health Belief Model to assess Knowledge and Attitude of Women Regarding Preconception Care - Maryam Moradi; Nasrin Fazeli; Talat khadivzadeh; Habibollah Esmaily (Mashhad University of Medical Sciences, 2020)
Background & aim: Effective preconception care requires childbearing women's knowledge and attitude to improve maternal and neonatal health by the early recognition of risk factors related to pregnancy. The aim of this study was to investigate knowledge and attitude of Iranian women regarding preconception health based on the health belief model. Methods: This cross sectional study was conducted on 110 married women aged 15-49 years in Mashhad, Iran, during 2016. Sampling was carried out through a multi-stage process. Data collected using questionnaires on demographic and obstetric data, knowledge and preconception risk assessment as well as health belief model questionnaire encompassing four constructs of perceived barriers, sensitivity, severity, and benefits, which considered as attitude. Data analysis was performed in SPSS using Pearson's correlation, Mann-Whitney U test, and Kruskal-Wallis test. Results: The knowledge of preconception care was poor in 36.4% of cases and moderate in 63.6% of participants. The score of attitude were neutral and good among 79.1% and 20.9% of participants, respectively. The scores of constructs of sensitivBackground & aim: Effective preconception care requires childbearing women's knowledge and attitude to improve maternal and neonatal health by the early recognition of risk factors related to pregnancy. The aim of this study was to investigate knowledge and attitude of Iranian women regarding preconception health based on the health belief model. Methods: This cross sectional study was conducted on 110 married women aged 15-49 years in Mashhad, Iran, during 2016. Sampling was carried out through a multi-stage process. Data collected using questionnaires on demographic and obstetric data, knowledge and preconception risk assessment as well as health belief model questionnaire encompassing four constructs of perceived barriers, sensitivity, severity, and benefits, which considered as attitude. Data analysis was performed in SPSS using Pearson's correlation, Mann-Whitney U test, and Kruskal-Wallis test. Results: The knowledge of preconception care was poor in 36.4% of cases and moderate in 63.6% of participants. The score of attitude were neutral and good among 79.1% and 20.9% of participants, respectively. The scores of constructs of sensitivity (80%), severity (77.3%) and perceived barriers (67.9%) were neutral, and only the construct of perceived benefit was at a good level among most women (63.3%). The scores of the all constructs had a significant correlation with scores of knowledge and attitude (P<0.05). Conclusion: The majority of women had moderate knowledge and neutral attitude regarding preconception care. Therefore, educational intervention based on a health belief model is recommended to improve the knowledge and attitude of women and develop preconception care behaviors in these individuals.ity (80%), severity (77.3%) and perceived barriers (67.9%) were neutral, and only the construct of perceived benefit was at a good level among most women (63.3%). The scores of the all constructs had a significant correlation with scores of knowledge and attitude (P<0.05). Conclusion: The majority of women had moderate knowledge and neutral attitude regarding preconception care. Therefore, educational intervention based on a health belief model is recommended to improve the knowledge and attitude of women and develop preconception care behaviors in these individuals.